(untitled) (UNWE Yearbook, 2008)
In the center of attention of the different directions for assuring of competitiveness of the tourism product, continuously stands the problem for assuring of its quantification. For the solving of this problem miscellaneous and quite often alternative solutions are being proposed. The common conclusion is, however, that many of these solutions are unacceptable. For the thorough solution of the problem in regard, we suggest two criteria to be used, namely the criterion for the production elaboration of the product and for its selling realization. For quantified expression of the first of these criteria, there could be used the indicators for the infrastructure; for the superstructure, for the product nomenclature and the range, for the quality, the price and the environmental sustainability.For the second criterion, which refers to the selling realization of the product, we apply the indicators for the form of servicing, for the work time of the tourism site, for the time for performing of the services, for the servicing environment, for the outlook of the servicing personnel, and for their attitude towards customers. In order to measure the values of the above-mentioned indicators, we suggest the technical, the organoleptic and expert method to be used. For the measurement of the competitiveness we implement the differentiated, the complex and the combined methods taking in account the parameter of significance, as well. This allows us to evaluate competitiveness not only by use of single indicators, but also by complex ones, thus defining and drawing out the general and the integral indicator for competitiveness.These is no doubt that the problems concerning the quantification of the tourism product competitiveness will find their further development in the evaluation of the work force competitiveness and in the search of dependencies upon the competitiveness of the created by it product in the financial and non-financial sphere.